Initial growth characteristics of gold thin films by a nozzle beam and ion-assisted deposition - Song, SK; Koh, SK; Lee, DY; Baik, HK (JAPAN SOC APPLIED PHYSICS, 2004)
The electrical conductance characteristics due to tunneling of Au films on glass substrates as a function of deposition rate and Ar+ ion current density have been investigated by in situ measurement. The onset thickness for conductance was 8.5-29 Angstrom lower than that obtained by other researchers due to the use of a nozzle beam in this study. The degree of agglomeration, I, attained its maximum value at a deposition rate R = 1.0 Angstrom/s. The degree of coalescence increased with increasing deposition rate. The onset thickness for conductance decreased to a nearly linear line with increasing ion beam irradiation.